Application of Design Thinking Techniques in Marketing of Fashion Apparel E - Commerce - Misra, Sudha; Arivazhagan, D. (Indian Journal of Marketing, 2017)
To apply design thinking towards creation of garments with an aim of solving size and fit issues and minimizing returns of sold merchandise in fashion e-commerce business, a study was done with Flipkart, one of the leading e-commerce companies to understand the problems they were facing with apparel returns in the year 2014 and 2015. Based on the product return data collected from online customers, a questionnaire was formulated and a study was done in Bangalore with 1000 people in the age group of 18 to 30 years to understand why people shop online for apparels and the issues faced by them. The questionnaire analysis showed that 42% of fashion apparel was returned because they were not the right size or fit, 19% were returned because of fabric quality issues, and 8% were returned because of problems with colour. A study was also conducted by observation and personal interviews with 150 customers at various offline stores in Bangalore for the identification of attributes related to the issues of size and fit. The problem areas identified in women-wear were issues with waist, bicep/sleeves, and chest. To combat these problems, various design ideas were proposed, and the selected designs were constructed and tested on a population of 100 women in the age group of 18 to 30 years of different body shapes for size and fit. It was concluded from the results that if the garments be created in such a way that it can fit many people of varying body shapes, it can drive businesses to improve the overall customer experience by reducing rampant returns of apparel.